Reseñas de libros, por Claudio Véliz, Ann Zammit, Antonio García, Alain Joxe, Amilcar Xá Peixoto, Eduardo Ortíz, A.G. Barnard, John Gittings, Jovan Milicevic, Amiti Pilowsky R., J.G. - Internacionales, Estudios (Estudios Internacionales, 1967)
-